Impact of an educational workshop on psychiatrists’ attitude towards psychosomatic medicine - Baessler, Franziska; Ciprianidis, Anja; Wagner, Fabienne L.; Zafar, Ali; Kanellopoulos, Thanos; Baumann, Tabea C.; Sandmann, Clara; Schultz, Jobst-Hendrik (BMC psychiatry, 2020)
Although psychosomatic medicine is not recognised as a medical specialisation globally, it has proven useful for treating many disorders in Germany. This paper reports on the impact of an educational workshop as a tool for raising awareness about psychosomatic medicine among international psychiatrists.